Work Absence in Europe - Bonato, Leo (IMF Working Papers; Working Paper ;, 2004)
Work absence is an important part of the individual decision on actual working hours. This paper focuses on sickness absence in Europe and develops a stylized model where absence is part of the labor-leisure decision made by workers and the production decision made by profit-maximizing firms, with insurance provisions and labor market institutions affecting the costs of absence. The results from a panel of 18 European countries indicate that absence is increased by generous insurance schemes where employers bear little responsibility for their costs. Shorter working hours reduce absence, but flexible working arrangements are preferable if labor supply erosion is a concern.